Perancangan Tata Letak Fasilitas Bisnis Retail dengan Pendekatan ARC dan TCR di Kota Depok - Alda Amelia Putri; Almay Sarwati; Davin Fesyahputra*; Serli Selvia (Jurnal Teknologi, 2023)
Service quality and comfort are largely determined by the people and the service environment. The aim of this research is to prove the effect of layout design with the ARC and TCR approaches in a service at Alfamart. The type of research used in this study qualitative and quantitative methods. Then the data obtained is carried out by taking primary data, by directly taking data in the field to find out the data needed as a basis for making decisions on making a solution layout. The high interconnectivity between rooms in the shop will make it easier for employees to work because employees will find it easier and faster to arrange goods and carry out work SOPs, of course this will affect work efficiency. Product grouping needs to be considered carefully because it will make it easier for consumers to find the items they are looking for. From the results of the study using the servicescape method, namely ARC and TCR, it was found that the layout update at Alfamart Tapos where the warehouse should be placed on the 1st floor. The location of the warehouse on the 1st floor aims to make it easier for employees to display and load and unload goods.